2012
DOI: 10.2514/atcq.20.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Workload for Work Organization in a Remote Tower Control Center

Abstract: This paper focuses on the role which workload can play for work organisation in a future remote control tower center. Nowadays you can find a control tower next to each airport. A tower is equipped with a team of controllers which maintain the declared surface movement rate under all weather conditions within the aerodrome visibility operational level (AVOL) while maintaining the required level of safety. Novel concepts for air traffic control (ATC) consider remotely controlling regional airports from a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…MRTO ATCOs have to maintain the same level of performance to ensure the safety of operations but at the cost of higher cognitive loads instead of physical demand. Previous research demonstrated that low workload had a negative influence on performance as it can aggravate boredom, and high workload can result in poor performance due to stress or overload (Eggemeier, ); however, high workload might provoke a strategy shift so that the operators perform well (Moehlenbrink, Papenfuss, & Jakobi, ). The high‐density of traffic and dynamic aircraft maneuvers in terminal airspace will increase ATCO's perceived workload.…”
Section: Resultsmentioning
confidence: 99%
“…MRTO ATCOs have to maintain the same level of performance to ensure the safety of operations but at the cost of higher cognitive loads instead of physical demand. Previous research demonstrated that low workload had a negative influence on performance as it can aggravate boredom, and high workload can result in poor performance due to stress or overload (Eggemeier, ); however, high workload might provoke a strategy shift so that the operators perform well (Moehlenbrink, Papenfuss, & Jakobi, ). The high‐density of traffic and dynamic aircraft maneuvers in terminal airspace will increase ATCO's perceived workload.…”
Section: Resultsmentioning
confidence: 99%
“…Design decisions for the work organization are based on quantitative human factors data, for example the influence of the new environment on the operators' workload (cf. [14]). …”
Section: Introductionmentioning
confidence: 93%
“…Erfurt (ERF) and Braunschweig (BWE) are selected as the two airports to be simulated. Global traffic parameters are determined, like traffic load and mix (departure/arrival ratio, visual flights/instrumental flights), which are close to a realistic heavy load at both airports [14]. Furthermore, the situations of interest are defined.…”
Section: First Stepmentioning
confidence: 99%
“…The workplace further included a touchscreen and microphone for the radio-and telephone communication, two displays representing the approach radar and paper strips for both airports. For a more detailed description of the simulation set-up refer to Moehlenbrink, Papenfuss & Jakobi (2011).…”
Section: Procedures and Apparatusmentioning
confidence: 99%